Giant cell lichenoid dermatitis within healed varicella zoster site - Yara Alghamdi; Bashaer Almahdi; Sahar Alsifri; Hassan Huwait; Abdulhadi Jfri (Clinical Case Reports, 2023)
Key Clinical Message There are dermatoses that arise within healed zosteriform sites, such as granulomas annulare, acneiform eruptions, psoriasis, lichen planus, and giant cell lichenoid dermatitis “GCLD.” Nonetheless, graft‐versus‐host disease should be considered and ruled out, especially in patients post‐bone marrow transplant. Herein, we report a case of GCLD manifesting within healed zosteriform sites.